A remark on Quantum Brownian Motion - Messer, Joachim; Justus Liebig University Giessen (My University, 2008)
An implicit exact solution is found for the semiclassical limit of Roumen Tsekov s quantum Smoluchowski equation for the harmonic oscillator.

Für den semiklassischen Grenzwert der von Roumen Tsekov formulierten Quanten-Smoluchowski-Gleichung für den harmonischen Oszillator wurde eine implizite exakte Lösung gefunden.
Keywords: Quantum Smoluchowski equation; harmonic oscillator; semiclassical limit; ddc:530